(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this big data era, from different sources a large data can be quickly generated. Access controlling in big data which contains a large amounts data becomes a difficult and challenging task. As per the needs of end users, it is required to build some mechanisms of access control to share the confidential information of end user to a specific authorized user. The main issue in cloud is security for access control. Cloud systems are protected by access control from the security issues. At present Cloud concentrates on various latest researches and implementations, which assures the secured and reliable file transfers. The access controls based on role, attribute, identification and hierarchical based access controls are in existing solutions. These are not enough to trust the cloud computing servers. The further future aim is to secure the files in storage by implementing a trusted model. The main aim of this presented paper is to give a fine-grained access control survey for the secure big data access with others. Access rights are provided by access control, in order to subject exact for object entity set. A set of rights are provided for a certain authorized person is done by Fine grained access control..